Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Di Madrasah Tsanawiyah Shirothul Fuqoha’ - Akhmad Husein Rifa’i; M. Ridwan Basalamah; Nurhidayah Nurhidayah (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This research was conducted at Madrasah Tsanawiyah Shirothul Fuqoha' . The type of research used is quantitative research where the data are expressed in numbers and analyzed by statistical techniques. The purpose of this study was to determine the effect of work motivation and work discipline of teachers at Madrasah Tsanawiyah Shirothul Fuqoha'. The independent variables used are work motivation and work discipline, while the variables used are teacher performance. The sample used in this study were 34 respondents who were teachers who worked at Madrasah Tsanawiyah Shirothul Fuqoha' . Data collection techniques using a questionnaire. The analytical method used is the instrument test, normality test, regression assumption test, multiple linear regression analysis, f test, t test and determination test, using SPSS 25 computer software for data processing. The results of this study indicate that work motivation has a positive and significant effect on teacher performance at Madrasah Tsanawiyah Shirothul Fuqoha', work discipline has a positive and significant effect on teacher performance at Madrasah Tsanawiyah Shirothul Fuqoha'. Keywords: Work Motivation, Work Discipline and Teacher Performance.